2000
DOI: 10.1152/jappl.2000.89.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Operation Everest III: role of plasma volume expansion onV˙o2maxduring prolonged high-altitude exposure

Abstract: We hypothesize that plasma volume decrease (DeltaPV) induced by high-altitude (HA) exposure and intense exercise is involved in the limitation of maximal O(2) uptake (VO(2)(max)) at HA. Eight male subjects were decompressed for 31 days in a hypobaric chamber to the barometric equivalent of Mt. Everest (8,848 m). Maximal exercise was performed with and without plasma volume expansion (PVX, 219-292 ml) during exercise, at sea level (SL), at HA (370 mmHg, equivalent to 6, 000 m after 10-12 days) and after return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
3
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 23 publications
7
52
3
3
Order By: Relevance
“…During the process of acclimatization, the initial increase in heart rate decreases, probably because of decreased cardiac responsiveness to b-adrenergic stimulation (12) and increased vagal tone (13,14). As stroke volume is decreased after prolonged altitude exposure because of a decrease in plasma volume, heart rate remains increased to maintain cardiac output at altitude (15,16). Even after acclimatization, maximum heart rate, maximum cardiac output, and maximum exercise capacity remain suppressed (17,18).…”
Section: At Altitudementioning
confidence: 99%
“…During the process of acclimatization, the initial increase in heart rate decreases, probably because of decreased cardiac responsiveness to b-adrenergic stimulation (12) and increased vagal tone (13,14). As stroke volume is decreased after prolonged altitude exposure because of a decrease in plasma volume, heart rate remains increased to maintain cardiac output at altitude (15,16). Even after acclimatization, maximum heart rate, maximum cardiac output, and maximum exercise capacity remain suppressed (17,18).…”
Section: At Altitudementioning
confidence: 99%
“…Reported maximal oxygen consumption was 54.4 ml/kg/min, Whereas Oelz (1986) estimated the mean of maximal oxygen consumption of mountain climbers 60 ml/kg/min (Oelz et al, 1986;Wagner, 2010). Robach et al found a 59% decrease in VO 2max at an altitude of 7,000 m by simulating the altitude in special rooms (Robach et al, 2000). Fitness status and type of equipment and tests used may be some possible reasons for these differences.…”
Section: Resultsmentioning
confidence: 99%
“…Нађена максимална потрошња кисеоника је износила 54.4 ml/kg/min, док је Оелз (1986) про-ценио средњу вредност максималне потрошње кисеоника код алпиниста од 60 ml/kg/min (Oelz, et al,1986;Wagner, 2010). Робах и сарадници су открили смањење од 59% у VO 2max на надморској висини од 7.000 метара, помоћу симулације виси-не у посебним просторијама (Robach, et al, 2000). Стање физичке спремности и врста опреме, као и тестови који су коришћени могу бити неки од мо-гућих разлога ових разлика.…”
Section: дискусијаunclassified
“…Also Cerretelli et al [24] concluded that still at an altitude of 2500 m, the VO 2max begins to fall between 5% and 10% comparing with sea level values. Other research works reporting changes after chronic acute HP, like published by Robach et al [25], simulate the ascent of 8 men to Everest with an hypobaric chamber (COMEX). In this study, the VO 2max decreased 59% at 7000 m above sea level.…”
Section: Maximal Oxygen Consumption (Vo 2max )mentioning
confidence: 99%